Relationship between Financial Indicators and Foreign Direct Investment in Eswatini - Kalu O Emenike; Nosipho Pearl Hlophe (AFRE (Accounting and Financial Review), 2020)
This study evaluates relationship between financial indicators and foreign direct investment (FDI) in Eswatini. The objective was to establish whether there exists significant relationship as well as causality between FDI and exchange rate, interest rate and inflation rate using annual data from 1980 to 2019. Unit root properties of the data were analysed using the Augmented Dickey Fuller test which showed that all data was stationary at first difference. The correlation results showed that there is a positive significant relationship between FDI and the exchange rate. The results also showed a positive but weak correlation for the interest rate as well as a weak negative correlation for inflation rate. The Granger causality test shows evidence of unidirectional causal relationship from exchange rate to FDI. In order words, exchange rate Granger causes FDI in Eswatini. We also document evidence of unidirectional causality from inflation rate to FDI. We recommend amongst others that Eswatini monetary authorities should continue to adopt fiscal and monetary policies that would contain inflation in the economy. DOI: https://doi.org/10.26905/afr.v3i1.4385